Plasma-derived exosomal miRNA as potential biomarker for diagnosis and prognosis of vector-borne diseases: A review - Venkatesan, Gokulakannan; Wan Ab Rahman, Wan Suriana; Shahidan, Wan Nazatul Shima; Iberahim, Salfarina; Muhd Besari@Hashim, Alwi bin (Frontiers in Microbiology, 2023)
Early disease diagnosis is critical for better management and treatment outcome of patients. Therefore, diagnostic methods should ideally be accurate, consistent, easy to perform at low cost and preferably non-invasive. In recent years, various biomarkers have been studied for the detection of cardiovascular diseases, cerebrovascular diseases, infectious diseases, diabetes mellitus and malignancies. Exosomal microRNA (miRNA) are small non-coding RNA molecules that influence gene expression after transcription. Previous studies have shown that these types of miRNAs can potentially be used as biomarkers for cancers of the breast and colon, as well as diffuse large B-cell lymphoma. It may also be used to indicate viral and bacterial infections, such as the human immunodeficiency virus (HIV), tuberculosis and hepatitis. However, its use in the diagnosis of vector-borne diseases is rather limited. Therefore, this review aims to introduce several miRNAs derived from exosomal plasma that may potentially serve as a disease biomarker due to the body’s immune response, with special focus on the early detection of vector-borne diseases.